Strong supply chains through resilient operations five principles for leaders to win in a volatile world - Gandhi, Suketu; He, Sherri; Hickerson, Tiffany; Lakner, Marc; Strohmer, Michael F. (Wiley, 2024)
"Business leaders around the world are undertaking the biggest remaking of operations since World War II. Post-pandemic, every organization is grappling with the consequences of global supply chains that for years were optimized only around lowest cost supplies and labor. That changed with the pandemic, the global labor shortage, war in Ukraine, and other crises. To meet those disruptions--companies must transform their operations. But how? Today's buzz around resilience and reshoring shows that firms are ready to fundamentally change their global value chain configuration and to move away from "lean" tenets that optimize for "cost -- cash -- service" to be more resilient. To succeed now, firms now they must become more flexible, more innovative, more relationship-driven, and more sustainable"--